Spatial Expression Pattern of ZNF391 Gene in the Brains of Patients With Schizophrenia, Bipolar Disorders or Major Depressive Disorder Identifies New Cross-Disorder Biotypes: A Trans-Diagnostic, Top-Down Approach. (3rd April 2021) - Ren, Hongyan; Meng, Yajing; Zhang, Yamin; Wang, Qiang; Deng, Wei; Ma, Xiaohong; Zhao, Liansheng; Li, Xiaojing; Wang, Yingcheng; Sham, Pak; Li, Tao
Abstract: The results generated from large psychiatric genomic consortia show us some new vantage points to understand the pathophysiology of psychiatric disorders. We explored the potential of integrating the transcription output of the core gene underlying the commonality of psychiatric disorders with a clustering algorithm to redefine psychiatric disorders. Our results showed that an extended MHC region was associated with the common factor of schizophrenia (SCZ), bipolar disorder (BD), and major depressive disorder (MDD) at the level of genomic significance, with rs7746199 ( P = 4.905e-08), a cis-eQTL to the gene ZNF391, pinpointed as a potential causal variant driving the signals in the region. Gene expression pattern of ZNF391 in the brain led to the emergence of 3 biotypes, independent of disorder. The 3 biotypes performed significantly differently in working memory and demonstrated different gray matter volumes in the right inferior frontal orbital gyrus (RIFOG), with a partial causal pathway arising from ZNF391 to RIFOG to working memory. Our study illustrates the potential of a trans-diagnostic, top-down approach in understanding the commonality of psychiatric disorders.